2018
DOI: 10.1097/md.0000000000009902
|View full text |Cite
|
Sign up to set email alerts
|

Epibulbar complex cartilaginous choristoma

Abstract: To newly describe the clinical and histopathological characteristics of epibulbar complex cartilaginous choristoma incidentally observed in a series of pterygium excision patients.Noncomparative case series with chart review of 8 patients.During a 4-year period, we identified 8 cases of conventional unilateral nasal subpterygial cartilaginous choristoma in 1799 pterygium patients and analyzed their clinicopathological features. The incidence rate of this entity is 0.44% in pterygium patients. All of the cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Most of the complex choristoma reported in literature were covered by mucous membrane [1, 6, 10]. A recent study identified complex cartilaginous choristoma covered by pterygium [9]. Even though the skin-covered surface and inferotemporal location in our case are reminiscent of limbal dermoid, the pathology report revealed complex choristoma.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Most of the complex choristoma reported in literature were covered by mucous membrane [1, 6, 10]. A recent study identified complex cartilaginous choristoma covered by pterygium [9]. Even though the skin-covered surface and inferotemporal location in our case are reminiscent of limbal dermoid, the pathology report revealed complex choristoma.…”
Section: Discussionmentioning
confidence: 61%
“…Limbal dermoid and dermolipoma are the most common type [8]. Complex choristomas are characterized by containing two or more ectopic tissues, which may include bone, cartilage, lacrimal gland tissue, muscle, nerve and adipose tissues [1, 4, 9]. In clinical practice, epibulbar complex choristomas are rarely seen, with diverse reported presentations, including circumferential or isolated epibulbar mass [1, 3], limbal tumor with corneal involvement [4], lateral canthal mass [3], aggregate of ectopic cilia in the upper eyelid [5], eyelid mass mimicking chalazion [6], or lacrimal caruncle mass [7].…”
Section: Discussionmentioning
confidence: 99%
“…Complex choristomas contain cells from two or more different tissue types, such as bone, cartilage, nerve, muscle, sebaceous secretions, or lacrimal tissues. Complex choristomas can be sporadic cases or can be associated with Goldenhar syndrome and LNSS (25)(26)(27)(28). For patient 24, the first biopsy of the nasal part showed a dermolipoma, and the result of the second biopsy of the temporal part disclosed a complex choristoma with immature hair follicle tissue, sebaceous gland, and hyperplasia of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…1 Choristomas have been reported at other anatomic sites in the head and neck, notably epibulbar and intraoral. 2,4 In the ear, typically they are located at the medial portion of the anterior wall of the EAC. 3 The majority of cases have been diagnosed in the second, third, or fourth decade of life and the vast majority of reported cases occurred in Asians.…”
mentioning
confidence: 99%
“…Ear, Nose & Throat Journal 103 (4) Ghiath Alnouri  https://orcid.org/0000-0002-2345-5476 Robert T. Sataloff  https://orcid.org/0000-0001-5146-6319…”
mentioning
confidence: 99%